Identifying suitable variables for visual aesthetic quality assessment of permanent forest reserves in the Klang Valley urban area, Malaysia - Mundher, Riyadh; Abu Bakar, Shamsul; Maulan, Suhardi; Gao, Hangyu; Mohd Yusof, Mohd Johari; Aziz, Azlizam; Al-Sharaa, Ammar (MDPI, 2023)
Permanent forest reserves (PFR) in urban areas are an integral aspect of the urban forest concept and the basis of a city’s green infrastructure. The preservation of natural forests in urban areas has become a widely researched topic due to the environmental, social, and economic benefits provided by it. Although several studies have shown that visual aesthetics play a role in preserving natural forests in urban areas, visual aesthetic value is typically not prioritized in preservation plans since it varies based on the physical characteristics of natural forests in urban areas, making it difficult to measure universally. Therefore, this research aims to identify the suitable variables for assessing the visual aesthetic quality of permanent forest reserves within urban areas in Malaysia. This study selected two permanent forest reserves based on four criteria. Data were collected via participant-generated images taken along selected forest trails based on participant visual aesthetic preferences. Researchers and experts analyzed and classified the data according to content to identify suitable visual aesthetic quality variables. This research identified 14 suitable variables for assessing the visual aesthetics of PFRs in urban areas, with a dominant preference for information-processing theory variables. Mystery was the most present variable for the visual aesthetic quality assessment of PFRs. Furthermore, participants’ educational and emotional backgrounds, categorized as design, environmental, social, and technical, impacted their visual aesthetic preferences. Our findings serve as a foundation for assessing the visual aesthetic quality of natural forests within urban areas in Malaysia.